2021
DOI: 10.3390/healthcare9111423
|View full text |Cite
|
Sign up to set email alerts
|

Survival of COVID-19 with Multimorbidity Patients

Abstract: Background: The outbreak of SARS-CoV-2 abruptly disseminated in early 2020, overcoming the capacity of health systems to respond the pandemic. It was not until the vaccines were launched worldwide that an increase in survival was observed. The objectives of this study were to analyse the characteristics of survivors and their relationship with comorbidities. We had access to a database containing information on 16,747 hospitalized patients from Mexico, all infected with SARS-CoV-2, as part of a regular follow-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 28 publications
0
1
0
Order By: Relevance
“…Multimorbidity with pre-existing health conditions [42], particularly asthma [43], has displayed a heightened risk of developing persistent symptoms and increased risk of COVID-19 fatality [44]. Multimorbidity has been positively associated with medication use, with 50% of adults in high-income countries taking up to 5 medications or more [45,46]. Poorer perceived health status may be considered a risk factor for long COVID symptoms, as observed in a study wherein 87% of the participants had a good self-reported health status before the pandemic but 83.3% reported moderate-to-poor self-reported health 6 months after initial onset [24].…”
Section: Principal Findingsmentioning
confidence: 99%
“…Multimorbidity with pre-existing health conditions [42], particularly asthma [43], has displayed a heightened risk of developing persistent symptoms and increased risk of COVID-19 fatality [44]. Multimorbidity has been positively associated with medication use, with 50% of adults in high-income countries taking up to 5 medications or more [45,46]. Poorer perceived health status may be considered a risk factor for long COVID symptoms, as observed in a study wherein 87% of the participants had a good self-reported health status before the pandemic but 83.3% reported moderate-to-poor self-reported health 6 months after initial onset [24].…”
Section: Principal Findingsmentioning
confidence: 99%
“…According to studies in Brazil, someone aged 60-79 years is 1.62 times more likely to die from COVID-19, and this will increase to 2.56 times when they are >80 years old (Garbin et al, 2022). In line with studies in Mexico at ages >80 years showing a death rate of 60.1% (Bustos-Vázquez et al, 2021). In addition, comorbidities previously suffered by patients also increase the mortality of people with COVID-19.…”
Section: Introductionmentioning
confidence: 85%
“…Diabetes Mellitus (DM) and cardiovascular disease are the most common comorbidities in COVID-19 sufferers (Bustos-Vázquez et al, 2021). Even the results of meta-analysis studies state that a person can have more than one comorbidity, which makes the patient's condition even more detrimental (de Almeida-Pititto et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation